Arabic To Tamil Translation: An Analytical Comparative Study Of Selected Quran Translation In Sri Lanka/ الترجمة من العربية إلى التاميلية: دراسة تحليلية مقارنة لترجمة مختارة لمعاني القرآن الكريم في سريلانكا - Meera Mohideen, Hassan Lafeer; KJ, Mohideen Abdul Kadir; Thalib, Ismail Mohamed; Hasmath, Athambawa Rayeesa (Ijaz Arabi Journal of Arabic Learning, 2025)
Translation of the Arabic language, especially the Qur'an, as Islam's primary and fundamental source, poses unique challenges due to its linguistic, semantic, and cultural depth. This study focuses on translating the Qur'an into Tamil by Jama'ath Ansaris Sunnathil Mohammadiyya in Sri Lanka, aiming to assess its accuracy and alignment with contemporary theories of religious translation. Given the widespread use of Tamil among Sri Lankan Muslims, this translation plays a significant role in their understanding of Islamic teachings. This fosters coexistence between the multiple Tamil-speaking communities in Sri Lanka. Using a descriptive-analytical method, this study analyses selected verses from the Tamil translation, evaluating its linguistic, semantic, and stylistic fidelity to the original Arabic. The study also examines the translator's approach, noting a mix of literal and interpretive strategies. While interpretive explanations are often included in parentheses, literal translation is used in cases of ambiguity. Furthermore, the translators demonstrate familiarity with Arabic dictionaries and exegetical sources, achieving clarity and accuracy in correctly presenting the meanings of the Qur'an. However, as found in other translations, there are shortcomings in the stylistic expression of Tamil and structural consistency. The study concludes that Jama'ath Ansaris Sunnathil Mohammadiyya successfully conveys the intended meanings of the Qur'anic text and fulfills its purpose to a large extent. The study offers practical recommendations for improving future translations, ensuring greater linguistic fidelity and cultural sensitivity, and reveals the contribution of this translation to fostering coexistence in the Sri Lankan context.